2017
DOI: 10.1038/tp.2017.61
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale interaction effects reveal missing heritability in schizophrenia, bipolar disorder and posttraumatic stress disorder

Abstract: Genetic susceptibility factors behind psychiatric disorders typically contribute small effects individually. A possible explanation for the missing heritability is that the effects of common variants are not only polygenic but also non-additive, appearing only when interactions within large groups are taken into account. Here, we tested this hypothesis for schizophrenia (SZ) and bipolar disorder (BP) disease risks, and identified genetic factors shared with posttraumatic stress disorder (PTSD). When considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 83 publications
4
32
0
Order By: Relevance
“…For these simulations, we used the dominant model to reduce the computational cost of enumerating all possible genotypes. For all other computations using animal trait data, we used the genotypic model, which includes the dominant model as a special case and generally enhances the power to infer associations relative to the dominant model [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For these simulations, we used the dominant model to reduce the computational cost of enumerating all possible genotypes. For all other computations using animal trait data, we used the genotypic model, which includes the dominant model as a special case and generally enhances the power to infer associations relative to the dominant model [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…We implemented and used a meta-analysis scheme for collective inference involving multiple sub-samples [ 12 , 29 ] (two in this work). Each sample was first divided into training and test sets, and the training sets were used to infer single-SNP and interaction parameters separately for each sub-sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It binds to motifs that regulate HIV gene expression [54]. A study has shown that the HIVEP1 gene was one of the highest ranked-genes to be related to mental disorders such as schizophrenia [37], bipolar disease (BP) and post-traumatic stress disorder (PTSD) [55]. The findings from our study have revealed an SNP (rs2228209) in the HIVEP1 gene that could potentially be linked to ADHD.A body of evidence has shown that SNPs in the integrin alpha 1 ITGA1 gene may cause ADHD.…”
Section: Locusmentioning
confidence: 99%